Influencia de la alimentación complementaria en la prevención de anemia ferropénica en niños de 6 a 12 meses, Hospital de Apoyo de Cangallo, Ayacucho, 2020. - Martínez Flores, Joaquín (2021)
Objective: To determine the influence of complementary feeding on the prevention of iron deficiency anemia in children from 06 to 12 months at the Hospital Apoyo Cangallo, 2020. Material and method: Study of descriptive type, transversal and relational level, the sample was 97 mothers, who responded to a questionnaire with characterization variables and a scale-type instrument of 15 items for the complementary feeding variable and 15 items for the variable prevention of iron deficiency anemia. The results were presented descriptively and Spearman's Rho test was used for the testing of hypotheses. Results: Participants found that 62.89% have regular complementary feeding, 21.65% optimal and 15.46% deficient. In the nutrition dimension there was a regular level of 59.79%, as in eating habits 61.86%. Likewise, 41.24% have a medium-favourable, 36.08% unfavourable and 22.68% favorable iron deficiency prevention. In its dimension consumption of ferrous sulfate, a moderately favorable level at 44.33%, in unfavourable medical controls at 43.30%. According to Spearman's correlation, a value of 0.516 was found, in addition to being significant (p-0.000). Conclusions: Complementary feeding influences the prevention of iron deficiency anemia in children from 06 to 12 months at the Hospital Apoyo Cangallo, 2020. Keywords: Nutrition, complementary feeding, prevention, anemia.